Learning from Exemplary Practices in International Disaster Management : A Fresh Avenue to Inform US Policy? - Moore, M.; Trujillo, H. R.; Stearns, B. K.; Basurto-Davila, R.; Evans, D. K. (2012)
The devastation of the U.S. Gulf Coast by Hurricane Katrina in August 2005 sparked widespread reconsideration of U.S. disaster management practices. While most of this inquiry has drawn on U.S. disaster experiences, countries throughout the world are also struck by natural disasters. We hypothesized that the disaster management experiences in other countries could represent a potentially valuable source of insight for the United States. Therefore, we identified and examined exemplary practices in disaster prevention/preparedness, response, and recovery/redevelopment from thirteen natural disasters in eleven countries, focusing in particular on areas that were problematic during the Hurricane Katrina response. Interviews with recognized international disaster management experts validated our preliminary assessments from these experiences and provided additional insights not gleaned from the literature. We discuss seven lessons from our analyses: (1) Different models, but common principles, underlie effective coordination; (2) Community participation is critical at all phases of the disaster management cycle; (3) Both technology and public awareness contribute to effective early warning; (4) Disaster management should be evidence-based when possible; (5) An early orientation to long-term recovery can be important; (6) Countries can and should learn from previous disaster experience; and (7) Disaster management solutions must be appropriate to the local setting. We also offer and discuss three recommendations: (1) Institutionalize the process of learning from international disaster management; (2) Apply relevant practices from international experience; and (3) Systematically define, identify, document and archive exemplary practices. We conclude that it is appropriate for the United States to learn from its past experiences, draw on the world of experience across borders, and prepare for the future. Our study offers concrete steps that can be taken in this direction.